言 (language) + 葉 (leaves) = 言葉 (spoken word) - Koh, Naomi Takatsuka (Nanyang Technological University, 2021)
言(language)＋葉 (leaves)＝言葉 (spoken word) explores how words and nature can be used as forms of expression. The project uses waka poetry as inspiration, studying the words and meanings of the poems written up to a thousand years ago, and visualizes them into illustrations that aim to transcend time and language. According to the Kokinshu compilation of poems, waka poetry is that which flows from the poet's heart through contact with beauties of nature or events of human life. These words intrigue all kinds of interpretations and meanings intended or not, by the poets. This project is a personal interpretation of those words – visually and through translation of language, and a method of expression to convey the possible nuances intended by the poets. The illustrations and editorial aim to stimulate the imagination and emotions of the viewer, such that even without an understanding of the language or contextual knowledge of the culture, they are able to form their personal interpretations of the original waka poetry.